VD_FINDINFO Jug / 2021 / 318 vom 31. März 2021 - VD Tribunal cantonal (2021)
TENTATIVEDROIT PÉNAL, MEURTRE, AGRESSION, LÉSION CORPORELLE SIMPLE, FIXATION DE LA PEINE | 123 CP, 139 CP, 22 ad 111 CP, 47 CP